Early minimally invasive image-guided eNdoscopic evacuation of iNTracerebral hemorrhage: a phase II pilot trial - Hallenberger, Tim Jonas; Fischer, Urs; Ghosh, Nilabh; Kuhle, Jens; Guzman, Raphael; Bonati, Leo Hermann; Soleman, Jehuda (Frontiers in Neurology, 2024)
BackgroundWhether minimally invasive endoscopic surgery (ES) improves survival and functional outcome in people with spontaneous supratentorial intracerebral hemorrhage (SSICH) is unknown.MethodsThis is a single-center pilot study performed between July 2021 to January 2023. Any supratentorial hematoma with a volume between 20 mL and 100 mL was endoscopically evacuated within 24 h after bleeding onset. Participants were followed-up for 6 months, assessing clinical and radiological outcomes. The primary feasibility outcome was satisfactory hematoma removal (<15 mL residual volume on the first postinterventional CT study) and the primary efficacy outcome was reaching a modified Rankin Scale 0–3 (mRS) at 6 months. Secondary outcomes were mortality and morbidity rates.ResultsTen participants (median age 72.5 years [IQR 67–81], 70% male, median baseline hematoma volume 34.1 [IQR 25.5–58.0]) were included. Satisfactory hematoma evacuation was achieved in 70% (7/10) with a median evacuation percentage of 69.5% [IQR 45.3–93.9%]. The median duration of surgery was 91 min [IQR 73–111]. Favorable outcome at 6 months was observed in 60% of the participants and improved from within 24 h before the intervention to the last follow-up (6 months). Five participants (50%) experienced a total of six complications, two recurrent bleedings, three pneumonias and one epilepsy. Mortality rate was 30%, while one participant died from pneumonia, one from a recurrent bleeding, and one participant due to a glioblastoma.ConclusionES appears to be feasible, with satisfactory hematoma removal being achieved in the majority of participants. Based on the descriptive results of this pilot trial, a national multicenter RCT comparing ES to best medical treatment is currently ongoingClinical trial registrationhttps://clinicaltrials.gov/, identifier NCT05681988.